Membangun Kemandirian Ekonomi Lokal melalui Semangat Koperasi Merah Putih di Kelurahan Karijawa Dompu - Nafisah Nurulrahmatiah; Ita Purnama; Nur Khusnul Hamidah; Putri Nabilah; Juhal Hidayat (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service activity aims to provide outreach to the Merah Putih Cooperative and prepare simple financial reports in Karijawa Village, Dompu Regency. This program stems from several key issues, such as limited access to capital, low cooperative literacy, and the lack of institutional economic governance at the village level as an effort to strengthen the local economy sustainably. Through a participatory, collaborative, and educational approach by the STIE Bima Impact Community Service Team in Karijawa Village, Dompu Regency, social identification and outreach were carried out in accordance with Law No. 25 of 1992. The outreach was carried out through face-to-face meetings and group discussions regarding the urgency of the Merah Putih Cooperative. This community service activity demonstrated an increase in community understanding of cooperatives as an instrument of sustainable local economic independence, as well as encouraging academic-community collaboration in the development of cooperatives and economic nationalism. This cooperative is expected to have a significant contribution in improving the sustainable economic welfare of the community.